2005
DOI: 10.1159/000085145
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Behaviour Group Therapy for Chronic Fatigue Syndrome: A Non-Randomised Waiting List Controlled Study

Abstract: Background: It has been demonstrated that individual cognitive behaviour therapy is an effective treatment for chronic fatigue syndrome (CFS). The aim of the present study was to investigate the effectiveness of cognitive behaviour group therapy (CBGT) in an unselected group of CFS patients. Additionally, pretreatment characteristics of CFS patients who improve after CBGT were explored. Methods: In a non-randomised waiting list controlled design, 31 patients were allocated to CBGT and 36 to the waiting list co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 52 publications
1
26
1
1
Order By: Relevance
“…There are also approaches for the delivery of CBT in groups of CFS patients [4,5] , but randomised controlled trials (RCTs) which examined the efficacy of group CBT for CFS in the past were either based on unpublished trials with small sample size [1,3] , combined CBT with graded exercise therapy for CFS [6] or produced inconsistent results [5] .…”
Section: Introductionmentioning
confidence: 99%
“…There are also approaches for the delivery of CBT in groups of CFS patients [4,5] , but randomised controlled trials (RCTs) which examined the efficacy of group CBT for CFS in the past were either based on unpublished trials with small sample size [1,3] , combined CBT with graded exercise therapy for CFS [6] or produced inconsistent results [5] .…”
Section: Introductionmentioning
confidence: 99%
“…We intentionally chose patients with chronic fatigue syndrome (CFS) because available treatment options for patients with CFS, such as cognitive behaviour therapy [19] or graded exercise therapy [20], are not generally effective [21, 22], or widely available and only used by some CFS patients because of their own individual attributional theories about this illness [23]. As patients with CFS are regularly seeking alternative treatments and may frequent healers, this would appear to be a reasonable intervention to evaluate.…”
Section: Introductionmentioning
confidence: 99%
“…Several articles [19][20][21][22][23][24] focused on probably the most systematically studied form of therapy, the CBT (yet some may argue that the primacy belongs to Rational Emotive Behavior Therapy). Linden et al [19] confi rmed that CBT is an effective method to treat generalized anxiety disorder (GAD) in a study comparing CBT (36 patients), control contact group (36 patients), and CBT after contact control period.…”
Section: Cognitive-behavioral Therapymentioning
confidence: 99%
“…Finally, I found the authors' statement in the abstract that 'differences between control and treatment group are comparable to or larger than those reported in studies on antidepressant drugs' amazing, as this article does not deal with this comparison directly and does not summarize the literature on pharmacological treatment of GAD. Bazelmans et al [20] found only a trend that Cognitive Behavior Group Therapy had a positive effect on fatigue in chronic fatigue syndrome, a condition notoriously resistant to any treatment. Unfortunately, they used therapists with no prior experience with this condition, which may have hindered the success of Cognitive Behavior Group Therapy.…”
Section: Cognitive-behavioral Therapymentioning
confidence: 99%